Writing emotions: theoretical concepts and selected case studies in literature - Jandl-Konrad, Ingeborg; Knaller, Susanne; Schönfellner, Sabine; Tockner, Gudrun (Lettre, 2017)
After a long period of neglect, emotions have become an important topic within literary studies. This collection of essays stresses the complex link between aesthetic and non-aesthetic emotional components and discusses emotional patterns by focusing on the practice of writing as well as on the impact of such patterns on receptive processes. Readers interested in the topic will be presented with a concept of aesthetic emotions as formative both within the writing and the reading process. Essays, ranging in focus from the beginning of modern drama to digital formats and theoretical questions, examine examples from English, German, French, Russian and American literature. Contributors include Angela Locatelli, Vera Nünning, and Gesine Lenore Schiewer